Floral visits of the wild bee, Lithurgus atratus, impact yield and seed germinability of okra, Abelmoschus esculentus, in Sri Lanka - Perera, Shashini; Karunaratne, Inoka (Journal of Pollination Ecology, 2019)
Bee-pollinated crops in landscapes with a low abundance of bees suffer from insufficient pollination. The present study investigates the effect of wild bee pollination on fruit and seed production in okra, Abelmoschus esculentus (L.) Moench. The study was conducted in a home garden, where an okra field was established for three pollination trials each to include 40 okra plants. For each trial, three sets of 25 flower buds were selected and tagged. One set was covered to deter bees, another set was kept open to enable bee visits and the other set was cross-pollinated by hand. Of the two species of bees, Tetragonula iridipennis (Smith) visited flowers for nectar while Lithurgus atratus Smith collected and carried pollen grains. The period of stigma receptivity and pollen availability coincided with the highest activity of L. atratus from 10.00 a.m. to 12.20 p.m. Bee-pollinated flowers had significantly enhanced okra pod length and diameter, seed number and seed germinability compared to the trial with flowers covered to deter bees. Hand pollinated flowers also produced significantly longer pods and a higher number of seeds with higher germinability. Although there was no significant difference in pod length and diameter and seed number between hand pollination trial and bee-pollinated trial, germinability of bee-pollinated seeds was significantly higher. Present study highlights the importance of the wild bee, L. atratus to enhance pod size, seed number and seed germinability in okra in Kurunegala, Sri Lanka.